Juridical Review of Local Government Policies in Overcoming Waste Problems in Kerinci District and Sungai Penuh City - Syurpana Nofanda (AHKAM, 2025)
Waste management challenges in Kerinci Regency and Sungai Penuh City present significant obstacles to the effective implementation of regional environmental policies. This study aims to analyze the juridical aspects of waste management policies, identify barriers to their implementation, and propose strategies to enhance the effectiveness of regulations grounded in good governance principles. Utilizing a normative legal research approach with statutory, conceptual, and case analyses, the study examines regulatory disharmony between national laws, including Law No. 18 of 2008 on Waste Management, Government Regulation No. 81 of 2012, and Presidential Regulation No. 97 of 2017, and local regulations in both regions. The findings reveal three primary issues: (1) inconsistency between national policies and regional regulations, notably Kerinci Regional Regulation No. 9 of 2013 and Regent Regulation No. 42 of 2018, as well as Sungai Penuh City Regional Regulation No. 9 of 2013 and Mayor Regulation No. 19 of 2024; (2) weak enforcement of legal instruments, including administrative sanctions and incentives; and (3) limited institutional effectiveness of TPS3R (3R Waste Processing Site) and insufficient community participation in the waste bank program. The study recommends harmonizing central and regional regulations, strengthening environmental law enforcement, developing economic incentives, and optimizing the role of community-based institutions such as BUM Desa (Village-Owned Enterprises) and KSM (Community Self-Help Groups) to establish a sustainable waste management system.